Practical radio-frequency handbook - Hickman, Ian. (Oxford ; Burlington, MA : Newnes, 2007)
Radio Frequency (RF) is the fundamental technology behind a huge range of modern consumer electronics and wireless communication devices, and this book provides a comprehensive and methodical guide to RF for engineers, technicians, enthusiasts and hobbyists with an interest in the electronics behind radio frequency communications. In Practical RF Handbook, Ian Hickman draws upon his own radio engineering background to develop a hands-on guide to the difficulties and pitfalls of RF design with a minimum of maths. A broad coverage includes devices, circuits, equipment, systems, radio propagation and external noise to fully acquaint the reader with the necessary circuit technologies and techniques. The fourth edition brings the book fully up-to-date with new advances in RF, including coverage of OFDM, UWB, WiFi and WiMax. * Practical coverage of the cutting-edge technology behind the fast-moving world of communications electronics * Real-world design guide for engineers, technicians and students, covering key principles with a minimum of maths * Updated throughout, including coverage of recent hot topics such as UWB, WiFi and WiMax.
Preface; Passive components and circuits; RF transmission lines; RF transformers; Couplers, hybrids and directional couplers; Active components for RF uses; RF small-signal circuitry; Modulation and demodulation; Oscillators; RF power amplifiers; Transmitters and receivers; Advanced architectures; Propagation; Antennas; Attenuators and equalizers; Measurements; Appendices; Index.
Previous ed.: 2002.
Includes bibliographical references and index.
Keywords: Radio circuits -- Design and construction -- Handbooks, manuals, etc; Electronic books